Vertical and horizontal inequality in Ecuador: The lack of sustainability - Iván Gachet; Diego F. Grijalva; Paúl Ponce; Damián Rodríguez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
We analyse vertical and horizontal inequality in Ecuador from a long-run perspective, as well as during and after the commodities boom. Using various data sources we show that Ecuador has made significant progress in reducing inequality, particularly since 2000. However, inequality has started to increase again starting in 2015. We provide preliminary evidence that the trend reversal is consistent with Ecuador's dependency on oil revenues. Once the commodities boom ended, government policies aimed at reducing inequality turned out to be unsustainable and inequality started to rise again.
Keywords: 330; Ecuador; inequality; poverty; horizontal inequality; vertical inequality; commodities boom; sustainability